Perancangan User Experience Aplikasi Website Computer Assisted Test (CAT) Menggunakan Five Planes Framework - Widyaningrum, Destriana (J-INTECH (Journal of Information and Technology), 2023)
Examinations in the school are still carried out conventionally, in a written method using a computer answer sheet. The development of a Computer Assisted Test (CAT) application website to replace the current exam implementation process is a problem for users who are not proficient in using computers. Users must understand new features and go through a long process of exam preparation stages. This research aims to design user experience, for the appearance of the Computer Assisted Test (CAT) application website, using the five planes framework. This method has elements that are done in stages from the lowest level to the top, starting from the strategy plane, scope plane, structure plane, skeleton plane, and surface plane. The result of this research is a user interface design prototype to be implemented on the CAT application website at a later time. The selection of the Five Planes framework with systematic stages is appropriate for designing user experience, starting from identifying the analysis of stakeholders business needs and objectives, directing the planning of a structured system function flow to create a website menu, to designing interfaces with attention to usability and aesthetics that are guided by design guidelines in selecting and displaying each visual element.